Kejahatan Korporasi Perpajakan dalam pelanggaran Hukum Pidana Pajak - Dharmasetya, Lani (Neolectura, 2023)
The purpose of this research and writing is to harmonize Article 43 of the KUP Law with Law Number 40 of 2007 concerning Limited Liability Companies. From this research, the results obtained show that there is a need to reformulate the formation of statutory regulations, namely reorganizing or renewing the process and mechanisms for making laws/other regulations to ensure that these regulations are in harmony/in line and do not conflict or contradict each other (non-contradictory). Many Minister of Finance regulations have been issued to regulate taxation and tax functions which are very vital in the country's economy.